2018
DOI: 10.1037/scp0000178
|View full text |Cite
|
Sign up to set email alerts
|

Maternal care for spiritual health of unborn child during pregnancy: A qualitative study with content analysis approach.

Abstract: Unborn child spirituality is a subject that has little regard in research. The purpose of this study is to explain the experiences of mothers regarding the spiritual well-being of their child during pregnancy. In a qualitative study, with purposive and easy sampling, 48 semistructured and in-depth interviews were conducted with 39 women who were pregnant or had recent experience of successful pregnancy. Data analysis was done using a conventional content analysis approach. The results showed that Iranian mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…This disparity is associated with the religion of individuals since women are less obliged to attend religious ceremonies in some religions, such as Islam. [ 46 47 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disparity is associated with the religion of individuals since women are less obliged to attend religious ceremonies in some religions, such as Islam. [ 46 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of some research studies, outdoor work is associated with lower involvement in religion. [ 47 ] Perhaps the exposure to diverse values and worldviews undermines religious commitment; therefore, relatively more traditional women tend to stay at home.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy requires mental preparation to accept the role of parents and planning and physical and mental preparations, especially for the mother (3,4). Therefore, a pregnancy without planning to have a child (Unplanned) (5) causes incompatibility (6,7). Research has demonstrated that UP are linked to depression, unhappiness, negative emotions, psychological instability (8, 9), con icts in relationships, diminished decision-making abilities, and overall quality of life more than planned pregnancies (8,10,11).…”
Section: Introductionmentioning
confidence: 99%